Sympathetic uveitis in children: a case report and literature review (Ukrainian Journal of Ophthalmology, 2025)
Background: Sympathetic ophthalmia is a rare autoimmune disease that presents as a bilateral granulomatous uveitis following a traumatic event or, less commonly, uniocular surgery.Purpose: To describe immunohistological and histomorphological data of a child who developed sympathetical ophthalmia in a healthy eye after a severe penetrating corneoscleral injury with contusion component.Material and Methods: We present clinical observation data of a boy of 6.5 years who developed sympathetic ophthalmia in the left eye 1.5 months after a penetrating ocular injury caused by a tree branch resulted in a severe corneoscleral laceration in the right eye.Types of treatment and data of clinical, imaging (ultrasound scanning and spectral-domain optical coherence tomography (SD-OCT)), pathohistological and immunological studies were described and reviewed.Conclusion: A high index of clinical suspicion and careful monitoring of the state of not only a traumatized eye, but also the fellow eye both in the early and late period after traumatic event are vital to ensure identification of initial signs of sympathetic inflammation (photophobia and tearing) and taking prompt adequate measures for the prevention of further development of sympathetic inflammation. The use of current imaging modalities (including ultrasound scanning and especially SD-OCT of the retina and optic nerve) enables early documentation of the initial signs of sympathetic inflammation. Further research is warranted to develop the targeted treatment methods that would take into account the components of the immunopathogenesis.
Keywords: sympathetic ophthalmia; trauma; children